Between Cultures : Europe and Its Others in Five Exemplary Lives - Seigel, Jerrold E. (Book collections on Project MUSE., 2016)
The remarkable individuals whose stories make up Jerrold Seigel's Between Cultures--Richard Burton, T.E. Lawrence, Louis Massignon, Chinua Achebe, and Orhan Pamuk--without ever seeking to exit from the ways of life into which they were born, all devoted themselves to exploring a second cultural identity as an intrinsic part of their first.